Analisa Proteksi Kebakaran Pada SPBU (Stasiun Pengisian Bahan Bakar Umum) Sulfat, Kota Malang, Jawa Timur - Daniel Baga; Yurnalisdel Yurnalisdel; Fifi Damayanti (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
This study focuses on evaluating fire protection systems at gas stations, which are vital infrastructure for fuel supply. The main objective of this study is to assess the availability of fire protection systems and the need for fire extinguishers to minimize the risk of fire. The methods applied include a quantitative descriptive approach through field observations, interviews, and documentation studies. The results show that gas stations have adequate supplies of water and light fire extinguishers. However, active protection systems, including fire detectors, sprinklers, and hydrants, are still inadequate, with a recorded reliability rate of only 24% and field facility completeness reaching 11.7%. For passive protection and evacuation facilities, the scores were 18.79% and 22.45%, respectively, which were considered quite good. These findings recommend the installation of at least three 9 kg fire extinguishers, four pillar hydrants, and thirty sprinkler points. By implementing these recommendations, it is hoped that gas stations can improve the safety of service users and reduce the risk of fire, as well as comply with existing safety regulations. This study is expected to serve as a reference for gas station managers and related parties in their efforts to improve fire protection and safety systems at public fuel supply facilities.